Energy management in IIUM library considering user behaviour - Ali Akhbar, Nur Azmira; Yusoff, Siti Hajar; Abdullah Din, Ummi Nur Kamilah; Midi, Nur Shahida (2018)
Electricity usage in a commercial building is a crucial issue and any over consumption should be prevented. Energy consumption in academic building is one of the causes that lead to high carbon emission. High carbon emission will cause global warming thus affects the environmental and health of the society. Variety users’ activity and room activities in academic building relatively related to the energy consumption due to the use of electricity. Therefore, this project analyzed users’ behavior and electricity consumption. It is done in order to determine the main factor that lead to high energy usage. Power consumption of identified appliances were analyzed. Through energy analysis, saving of electricity can be done by minimizing the power consumption of electrical appliances and avoiding behavior that lead to wastage of energy. Based on this issue, data regarding all activities in the building has been collected. Questionnaires and online surveys were distributed among students and staffs of the library to gain insight observation on how electricity inside the building is utilized. A system has been designed to simulate the scenario and to give out alert on power consumption to the management team.